Measuring measuring social tourism sustainability in Porto municipality : the views of residents - Silva, Goretti (2022)
In the previous decade, tourism planning and destination management efforts have focused on sustainability, particularly in its environmental pillar. In the last years though (and specially in destinations with high growing rates and risks of over tourism) the social dimension has gained importance, also as consequence of increasing awareness about the need and relevance of governance for the sector. The aim of this paper is thus to address the phenomenon of (over)tourism in Porto area, and more recently, the zero tourism: how is tourism affecting residents? life from their own perspective? ETIS - European toolkit for sustainable destination management was the indicator system used to develop this exercise, once it has already been adapted to the country's reality by the national tourism authority (Turismo de Portugal). Results concerning residents? and local authority representative?s feelings about tourism and implications to local community, both from an economic and cultural environment perspectives, how these affect quality of life in the historical centres, are described. The study exposes different perspectives both with regard to advantages and disadvantages, but overall there is evidence that tourist development is widely accepted, considering it does not penalize the well-being of the resident population. Finally, results are discussed considering existing literature focusing on tourism sustainability in Porto, on a pre-covid and postcovid perspective.